Scaling social impact in women-led social enterprises in developing countries: a knowledge-based perspective - Hafiz, Nusrat; Mohiuddin, Md. Fazla; Abdul Latiff, Ahmad Shaharudin; Md. Yasin, Ida; Abd Wahab, Sazali; Abdul Latiff, Ahmed Razman (Emerald Publishing, 2023)
Purpose: Although scaling is considered a “hot topic”, very little is known about how knowledge management (KM) assists in scaling social impact. To fill this gap, the authors draw on knowledge-based and social capital theories and investigate how various KM practices and external networks (e.g. bridging social capital) affect scaling social impact in developing countries. Design/methodology/approach Applying structural equation modeling (SEM) with AMOS version 23, the authors conducted a survey with 354 women leaders who are working in women-led social enterprises in Dhaka, Bangladesh. Findings: The authors found that knowledge codification, training and mentoring, and bridging social capital are positively and significantly associated with scaling social impact. Originality/value: This is one of the pioneering study that explore how KM impacts scaling social impact for women-led social enterprises in the context of a developing country. The authors also extend knowledge-based theory by applying it at the individual level. Finally, the authors enhance the understanding of women entrepreneurship by showing that women entrepreneurs in developing countries are also utilizing bridging social capital to overcome challenges associated with scaling social impact.